1983
DOI: 10.1302/0301-620x.65b3.6841390
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the adolescent growth spurt on early posterior spinal fusion in infantile and juvenile idiopathic scoliosis

Abstract: Winter RB, Moe JH. The results of spinal arthrodesis for congenital spinal deformity in patients younger than five years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 10 publications
0
45
0
2
Order By: Relevance
“…Thoracic cage size modification following spinal arthrodesis appears to be a progressive process involving multiple skeletal parameters simultaneously. In young children with progressive deformity, there is a decrease of longitudinal growth and a loss of the normal proportionality of trunk growth [5,6,10,12]. As the spinal deformity progresses by a ''domino effect'', not only spinal growth is affected, but also the size and shape of the thoracic cage are modified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic cage size modification following spinal arthrodesis appears to be a progressive process involving multiple skeletal parameters simultaneously. In young children with progressive deformity, there is a decrease of longitudinal growth and a loss of the normal proportionality of trunk growth [5,6,10,12]. As the spinal deformity progresses by a ''domino effect'', not only spinal growth is affected, but also the size and shape of the thoracic cage are modified.…”
Section: Discussionmentioning
confidence: 99%
“…As a ''domino effect'', the distortion of the thorax will eventually interfere with lung development and cardiac function, leading those children to develop thoracic insufficiency syndrome (TIS) [3] and cor pulmonale [1] which can be lethal in most severe cases [2,4,5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Methods used for evaluation of vertebral growth [18] or vertebral remodelling after spine surgery are based on measurements of distances between selected points on radiographs of the concerned vertebrae [11,12,14,17] or the disc [15,16] for indirect estimation of the vertebral growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that the described method is easy to apply and has satisfactory accuracy for in vivo longitudinal studies of the volume of the vertebral body on radiographs and CT scans. strumentation and fusion [2,7,12,13,16]. The conclusion drawn from these studies are based exclusively on measurements of the vertebral height and width on radiographs, or on evaluation of certain CT scan variables [23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This is certainly true with regard to sex predilection: the female-to-male ratio is 1:1 in children between three and six years of age, 2:1 to 4:1 overall in children who are at least three but less than ten years of age 5 , and 8:1 by the time the children are ten years of age, which is a ratio close to that reported for patients with adolescent idiopathic scoliosis 1 . Hefti and McMaster reported that males are normally diagnosed with juvenile idiopathic scoliosis at approximately five years of age, whereas females are diagnosed at approximately seven years of age 6 . This difference, coupled with the fact that most males become skeletally mature at a later age than females, means that the risk of curve progression is higher for males with early onset juvenile idiopathic scoliosis than for females.…”
Section: Natural History and Epidemiologymentioning
confidence: 99%